Plagiarism in Higher Education and Impacts - Rinaldi Pahlevi; Suyono Thamrin; Irdam Ahmad; Rusnah Setiani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The development of information technology has made it easy to access all information according to certain interests and purposes, including bringing a tendency to plagiarism. In the world of education, plagiarism can occur starting from various levels of education, including at the university level. Plagiarism at the university level carried out by various circles can be categorized into plagiarism carried out intentionally or unintentionally both on all or part of the work of others without including adequate reference sources in order to achieve certain goals or targets. The impact of plagiarism can occur in three aspects, namely, the impact on the perpetrators of plagiarism, especially the losses that will be felt in the future, the development of science that will be hampered, and the future of educational institutions in Indonesia related to public trust and the quality and value of its usefulness which results in a decrease in the quality of human resources in an effort to advance the nation and state.